Current Practices and Perceptions of Admission Criteria at Physical Therapist Education Programs in the United States. Issue 1 (March 2019) - Mitchell, Katy; Ellison, Jennifer; Gleeson, Peggy
Abstract : Introduction: Entry-level Doctor of Physical Therapy (DPT) programs in the United States (US) have developed admission criteria (AC) to identify applicants most capable of program success; however, there is little evidence to support these criteria. The purpose of this study was to 1) gather data on the use and weighting of AC, 2) explore the perceptions of the value of AC, 3) explore a possible discrepancy between the use of AC and their perceived value, 4) determine whether differences in AC exist between programs with higher versus lower licensure pass rates, higher versus lower student retention rates, and across geographic regions in the US. Subjects: All DPT programs (N = 218) in the US accredited by the Commission on Accreditation of Physical Therapy Education were eligible for recruitment in this study. The survey was completed by a program director, an admission committee chair, or a faculty member familiar with the program's admission process. Of the 218 programs invited to complete the survey, 73 responded with a response rate of 33.5%. Methods: An anonymous, 30-item survey was used for data collection. Descriptive and comparative statistical methods were used on the data as a whole and by subgroups. Results: Undergraduate overall grade point average (GPA), math/science GPA, or verbal and quantitative Graduate Record Examination (GRE) scores were weighted heavily in admission decisions. The personal essay, volunteer hours, and letters of recommendation were not considered predictive of program success. There were significant differences in the proportion of programs that use the verbal and quantitative GRE scores when subdivided by licensure pass rate, either ≥95% or <95% ( P = .005 and P = .049, respectively). There were no proportional differences in the utilization or weighting of criteria when programs were divided by student retention rate, either ≥95% or <95%. Geographic differences were found in the use and weighting of AC when comparing the West region with other parts of the US. Conclusion: Previous literature suggests that undergraduate GPA is the best predictor of success in a DPT program; however, this study found no significant differences between the use or weight given to the GPA on licensure examination pass rates or student retention rates. Programs may wish to reconsider requiring a number of criteria that were not weighted heavily or considered to be a top predictor of success in a DPT program, particularly those criteria that are resource intensive.